2018
DOI: 10.1186/s13020-018-0199-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different principles of Traditional Chinese Medicine treatment on TLR7/NF-κB signaling pathway in influenza virus infected mice

Abstract: BackgroundInfluenza virus is a single-stranded RNA virus that causes influenza in humans and animals. About 600 million people around the world suffer from influenza every year. Upon recognizing viral RNA molecules, TLR7 (Toll-like receptor) initiates corresponding immune responses. Traditional Chinese Medicines (TCMs), including Yinqiao powder, Xinjiaxiangruyin and Guizhi-and-Mahuang decoction, have been extensively applied in clinical treatment of influenza. Although the therapeutic efficacy of TCMs against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…C57Bl/6J and SCID (severe combined immune deficiency) mice were purchased from the Model Animal Research Center, Nanjing University (Nanjing, China). Tlr7-KO mice were obtained from The Jackson Laboratory (Bar Harbor, Maine) and all the KO mice were backcrossed with C57BL/6 mice over 10 generations (32). All mouse protocols followed the National Institutes of Health guidelines for the care and use of mice and were approved by the Institutional Animal Care and Use Committee of Nanjing University (Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…C57Bl/6J and SCID (severe combined immune deficiency) mice were purchased from the Model Animal Research Center, Nanjing University (Nanjing, China). Tlr7-KO mice were obtained from The Jackson Laboratory (Bar Harbor, Maine) and all the KO mice were backcrossed with C57BL/6 mice over 10 generations (32). All mouse protocols followed the National Institutes of Health guidelines for the care and use of mice and were approved by the Institutional Animal Care and Use Committee of Nanjing University (Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…In recent research, it has been reported that TCM enhanced antibody production, maintain the balance between Th1 and Th2/Th17 cells for the prevention of viral pneumonia (Fu et al,2018). This study has proved that BFQW had a better therapeutic effect in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 52%
“…The expression of TLR7, MyD88, IRAK4, and NF-κB was signi cantly decreased in the YQP group, but the therapeutic effect of YQP on TLR7 KO mice was poor. This suggests that YQP may play an anti-in uenza role by regulating TLR7/NF-κB [30] . As for the MAPK pathway, some studies have reported that Raf/MEK/ERK signaling plays an important role in in uenza virus proliferation.…”
Section: Discussionmentioning
confidence: 94%